The Italian cross-cultural adaptation of the Social Vulnerability Index - Mangini, Gloria; Festari, Cristina; Ottaviani, Silvia; Tagliafico, Luca; Di Cara, Gianluca; Nencioni, Alessio; Monacelli, Fiammetta, Delphi Consensus Panel (Frontiers in Public Health, 2025)
BackgroundSocial vulnerability is a key health domain that is associated with frailty and disability in older adults, informing clinical trajectories and outcomes both on an individual and at a population level. The underlying concept is that frailty develops with the accumulation of physical, psychological, and social deficits, and the identification of losses in the social domain may allow for designing tailored interventions in a timely fashion. The aim of the present study was to adapt the Social Vulnerability Index (SVI) to the Italian language and culture for these purposes.MethodsThe Italian version of the SVI (SVI-I) has been developed through a comprehensive cross-cultural adaptation of the original Canadian SVI. This process involved four steps: initial translation, synthesis of translations, back translation, and a Delphi procedure.ResultsThe result of the study is the face-valid 38-item SVI-I. Based on the Delphi procedure, the SVI-I can be administered to Italian-speaking, over-65, community-dwelling individuals not affected by cognitive decline.ConclusionThis study develops the first index to measure social vulnerability in the Italian-speaking population, aiming at a multidimensional approach to address social and healthcare needs. If proven effective in subsequent validation studies, it may enhance geriatric assessments, improve early social vulnerability detection, and support tailored care plans.